The Maastricht Convergence Criteria and Optimal Monetary Policy for the EMU Accession Countries. - Anna Lipińska (European Central Bank (ECB), 2008)
The EMU accession countries are obliged to fulfill the Maastricht convergence criteria prior to entering the EMU. This paper uses a DSGE model of a two-sector small open economy, to address the following question: How do the Maastricht convergence criteria modify optimal monetary policy in an economy facing domestic and external shocks? First, we derive the micro founded loss function that represents the objective function of the optimal monetary policy not constrained to satisfy the criteria. We find that the optimal monetary policy should not only target inflation rates in the domestic sectors and aggregate output fluctuations but also domestic and international terms of trade. Second, we show how the loss function changes when the monetary policy is constrained to satisfy the Maastricht criteria. The loss function of such a constrained policy is characterized by additional elements penalizing fluctuations of the CPI inflation rate, the nominal interest rate and the nominal exchange rate around the new targets which are potentially different from the steady state of the unconstrained optimal monetary policy. Under the chosen parameterization, the unconstrained optimal monetary policy violates two criteria: concerning the CPI inflation rate and the nominal interest rate. The constrained optimal policy results in targeting the CPI inflation rate and the nominal interest rate that are 0.7% lower (in annual terms) than the CPI inflation rate and the nominal interest rate in the countries taken as a reference. The welfare costs associated with these constraints need to be offset against credibility gains and other benefits related to the compliance with the Maastricht criteria that are not modelled.
Keywords: F41; E52; E58; E61; 330; EMU accession countries; Maastricht convergence criteria; optimal monetary policy; Europäischer Stabilitätsmechanismus; Geldpolitik; EU-Mitgliedschaft; Europäische Integration; EU-Staaten